2022
DOI: 10.1002/hep.32298
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy promotes hepatic cystogenesis in polycystic liver disease by depletion of cholangiocyte ciliogenic proteins

Abstract: Backgrounds and Aims: Polycystic liver disease (PLD) is characterized by defective cholangiocyte cilia that regulate progressive growth of hepatic cysts. Because formation of primary cilia is influenced by autophagy through degradation of proteins involved in ciliogenesis, we hypothesized that ciliary defects in PLD cholangiocytes (PLDCs) originate from autophagy-mediated depletion of ciliogenic proteins ADP-ribosylation factor-like protein 3 (ARL3) and ADP-ribosylation factor-like protein 13B (ARL13B) and ARL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Supporting the proposal that defective cilia are linked to BA pathogenesis, we demonstrated that LKO mice have decreased number of cilia, although the direct links between absent Pkd1l1 and reduced ciliary development remain to be understood. Among the possibilities are that since Pkd1l1 is shown in select models to be present in primary cilia and plays a role in ciliary calcium signaling,44 its absence could plausibly lead to aberrant intracellular signaling that induces the development of the reactive ductular phenotype 45. Further, repression of other members of the polycystin family ( Pkd1 and Pkd2 ) causes an elongated/twisted cilia46 rather than an overall decrease in cilia, as seen here.…”
Section: Discussionmentioning
confidence: 74%
“…Supporting the proposal that defective cilia are linked to BA pathogenesis, we demonstrated that LKO mice have decreased number of cilia, although the direct links between absent Pkd1l1 and reduced ciliary development remain to be understood. Among the possibilities are that since Pkd1l1 is shown in select models to be present in primary cilia and plays a role in ciliary calcium signaling,44 its absence could plausibly lead to aberrant intracellular signaling that induces the development of the reactive ductular phenotype 45. Further, repression of other members of the polycystin family ( Pkd1 and Pkd2 ) causes an elongated/twisted cilia46 rather than an overall decrease in cilia, as seen here.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, activation of TGR5 on cholangiocyte cilia depresses cAMP formation and proliferation while the same signal in non-ciliated cholangiocytes enhances intracellular cAMP and cell growth. The important role of TGR5 as a possible regulator of biliary mass suggests that this receptor is a possible target in human diseases characterized by uncontrolled cholangiocyte growth, such as cholangiocarcinoma[ 25 ] or polycystic liver disease[ 26 ]. More recently, other BA receptors, such as the S1PR2, have been identified on cholangiocytes[ 27 ].…”
Section: Bas/biliary Epithelia Interactionsmentioning
confidence: 99%
“…TGR5 is a receptor related to the cAMP signaling pathway and one of the main sensory/signaling proteins of the primary cilium. [100][101][102][103] In PLD, due to the reduced levels of ARL3 and ARL13B, TGR5 is abnormally expressed in the apical region of the primary cilium and its activation promotes an increase in intracellular levels of cAMP, an event that favors the cell proliferation of cystic cholangiocytes and, consequently, the hepatic cystogenesis. Pharmacological inhibition of autophagy by mefloquine and verteporfin restores levels of ARL3 and ARL13B and restores proper localization of TGR5, thus reducing hepatic cystogenesis.…”
Section: Increased Autophagymentioning
confidence: 99%
“…TGR5 is a receptor related to the cAMP signaling pathway and one of the main sensory/signaling proteins of the primary cilium. 100–103 …”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation